The Effectiveness Of High-Flow Nasal Cannula (HFNC) Therapy On Improvement Of Oxygen Saturation With Acute Breathing Failure In Covid-19 Patients (Literature Study) - Syafruddin Ali Salaka; Hardiyati .; Iqra S; I Made Sudarta (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2022)
The Covid-19 pandemic has hit the world today, causing a health crisis, a humanitarian crisis and a socio-economic crisis. Covid-19 is classified as SARS-CoV-2 which was first discovered on December 1, 2019 in Wuhan, China. The COVID-19 pandemic has caused an increase in new cases in a short time, resulting in an increase in the use of the necessary supporting facilities and infrastructure. The use of Flow Nasal Cannula (HFNC) is very helpful in increasing oxygen saturation in patients with respiratory failure despite being given oxygen through a 15 liter per minute nasal cannula. Objective: To synthesize literature and research documents that identify the effectiveness of High-flow nasal cannula (HFNC) therapy. On increasing oxygen saturation with acute respiratory failure in Covid-19 patients. Methods: This study uses a literature study whose articles were obtained from 3 databases, namely Google Schoolar, Pub Med, and GARUDA (Garba Reference Digital) indexed from DOAJ (Directory of Open Access Journals) Elsevier, Wiley Online Library, Sinta 3, Scopus, and Springer. Results: The administration of High-flow nasal cannula (HFNC) therapy to increase oxygen saturation with acute respiratory failure in Covid-19 patients was able to have a positive impact on increasing oxygen saturation with acute respiratory failure in Covid-19 patients. Conclusion: There is a significant effect on the administration of High-flow nasal cannula (HFNC) therapy on increasing oxygen saturation with acute respiratory failure in Covid-19 patients.